ANÁLISE DE MATERIAIS PARA DESEMPENHO ACÚSTICO EM SISTEMAS DE PISOS QUANTO AO ISOLAMENTO DE RUÍDO DE IMPACTO - Martins, Daniele; Santos, Marcus; Scherer, Cláudio; Kist, Lidiane (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The challenge of the acoustical comfort of the buildings for the designers is to implement a solution in which the materials used in the floor system can simultaneously reduce the sound and be economically viable, according to the minimum, intermediate or higher level as stated in NBR 15575-3: 2013. This work aimed to analyse the mechanical properties of different materials, their weighted standardized impact sound pressure level (L'nt, w) as well as their financial cost for the implantation of a floor system that absorbs the sound. Therefore, the impact noise test was performed in loco according to ISO 16383-2: 2015 and ISO 717-2: 2013.The tested floor systems consist of the following acoustic insulation materials: acoustic insulation adhered to slabs without subfloor, acoustic blanket under the self-levelling mortar, self-levelling mortar for subfloor, and corrugated blanket with subfloor formed by cement, sand and water. It was verified that the system composed of acoustic insulation for underlayment with self-levelling mortar presented worse performance and lower cost, while the floor system formed by slab with 5cm underlayment and 8 / 4mm mantle presented better performance, but higher cost.